Dynamics of Larix (Mill.) species in Siberia during the last 50,000 years inferred from sedimentary ancient DNA - Schulte, Luise (2022)
The deciduous needle tree larch (Larix Mill.) covers more than 80% of the Asian boreal forests. Only a few Larix species constitute the vast forests and these species differ markedly in their ecological traits, most importantly in their ability to grow on and stabilize underlying permafrost. The pronounced dominance of the summergreen larches makes the Asian boreal forests unique, as the rest of the northern hemisphere boreal forests is almost exclusively dominated by evergreen needle-leaf forests. Global warming is impacting the whole world but is especially pronounced in the arctic and boreal regions. Although adapted to extreme climatic conditions, larch forests are sensitive to varying climatic conditions. By their sheer size, changes in Asian larch forests as range shifts or changes in species composition and the resulting vegetation-climate feedbacks are of global relevance. It is however still uncertain if larch forests will persist under the ongoing warming climate or if they will be replaced by evergreen forests. It is therefore of great importance to understand how these ecosystems will react to future climate warmings and if they will maintain their dominance. One step in the better understanding of larch dynamics is to study how the vast dominant forests developed and why they only established in northern Asia. A second step is to study how the species reacted to past changes in the climate. The first objective of this thesis was to review and identify factors promoting Asian larch dominance. I achieved this by synthesizing and comparing reported larch occurrences and influencing components on the northern hemisphere continents in the present and in the past. The second objective was to find a possibility to directly study past Larix populations in Siberia and specifically their genetic variation, enabling the study of geographic movements. For this, I established chloroplast enrichment by hybridization capture from sedimentary ancient DNA (sedaDNA) isolated from lake sediment records. The third ...